STUDI PENDAHULUAN UNSUR TANAH JARANG PADA LEMPUNG BERSISIK MÈLANGE BOBONARO DI DESA OBEN, KECAMATAN NEKAMESE, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - Kotta, Herry Zadrak; Mella, Welhelmus; Suwari; Banunnaek, Noni (Jurnal Ilmu Tanah dan Lingkungan, 2024)
The location of the investigation area is in Oben Village, Nekamese District, Kupang Regency, East Nusa Tenggara Province with coordinates 123° 40'40” E - 123° 41'20” E and 10° 16'0” S - 10° 16'40” S. The geology of the study area is generally occupied by mixed rocks dominated by a gray clay, blackish brown, reddish brown, with foreign chunks consisting of peridotite, sedimentary rock consisting of brown and reddish reddish limestone, silt, micaceous sandstones, metamorphic rock: chlorite schist, with quartzite veins. Of the five samples analyzed, namely four samples of soil matrix and one sample of Peridotite, the following results were obtained: six rare earth elements were contained in 4 samples of the soil matrix, namely Yttrium (Y): 3.63 – 68.75 ppm, Praseudymium (Pr): 7.38 – 38.38 ppm, Scandium (Sc): 4.83 – 4.93 ppm, Lanthanum (La): 21.48 – 91.03 ppm, Cerium (Ce): 32.48 – 184.85 ppm, and Neodymium (Nd): 9.4 – 57 ppm specifically for sample 1 also contains 3 rare earth elements, namely: Gadolinium (Gd): 3.48 ppm concentration the average is lower than its abundance in nature, Samarium Sm: 13.1 ppm, and Dysprosium: (Dy): 6.88 ppm. For rock samples only contain Praseudymium (Pr): 7.78 ppm and Cerium (Ce): 87.88 ppm.